MRI OF CONGENITAL SUB-GLOTTIC HEMANGIOMA: A CASE REPORT - BALACHANDRA, Shashilekha; PEKANAN, Patchrin; PORNKUL, Ratanaporn (The ASEAN Journal of Radiology, 2023)
Sub-glottic hemangioma is generally a benign lesion which causes upper airway obstruction and dyspnea. We reported MRI findings in a case of sub-glottic hemangioma. A 2 month-old Thai girl presented with progressive dyspnea and upper airway obstruction secondary to a mass on the left side of the sub-glottic trachea. Conventional radiographs, CT scan of the neck and indirect laryngoscopy prior to MRI study failed to reveal the presence of the lesion. Repeated laryngoscopy after MRI scan showed a mass in the sub-glottic trachea corresponded to the MRI findings. Hemangioma was diagnosed because this child also had cutaneous hemangioma in the occipital region. The potential lethal nature of these lesions was emphasized.